Effects of Healthy Aging on Tongue‐Jaw Kinematics During Feeding - Punacha, Shreyas; Huang, Kevin; Arce‐McShane, Fritzie I. (Journal of oral rehabilitation, 2025)
ABSTRACT Background Several age‐related oral health problems have been associated with neurodegenerative diseases such as Alzheimer's Disease (AD) and Parkinson's Disease (PD). However, the distinction between oromotor dysfunctions in healthy aging and pathological aging remains unclear. This is partly because changes in the cortical and biomechanical (“neuromechanical”) control of oromotor behaviour in healthy aging are poorly understood. Objectives The aim of the study was to evaluate age‐related changes in tongue and jaw kinematics during natural feeding behaviour in non‐human primates. Methods We captured three‐dimensional tongue and jaw movements in young and aged rhesus macaques (Macaca mulatta) using high‐resolution biplanar videoradiography combined with X‐ray Reconstruction of Moving Morphology (XROMM). This approach allowed precise tracking of tongue and jaw kinematics during natural feeding behaviour. Tongue stereotypy and velocity were quantitatively assessed, along with the temporal coordination between tongue and jaw movements. Feeding performance was measured using frequency and duration of food manipulation, chewing, and swallowing. Results Older subjects exhibited reduced stereotypy in tongue movements during chews and greater lags in tongue movements relative to jaw movements compared to younger subjects. Conclusions Our findings reveal age‐related changes in tongue and jaw kinematics, which may indicate impaired tongue‐jaw coordination. These results have important implications for the discovery of potential neuromechanical biomarkers for early diagnosis of AD.